Exploring immunisation inequities among migrant and refugee children in New Zealand. Issue 12 (2nd December 2018) - Charania, Nadia A.; Paynter, Janine; Lee, Arier C.; Watson, Donna G.; Turner, Nikki M.
ABSTRACT: Migrants may experience immunisation inequities compared with the host population related to barriers with accessing immunisations in their home countries, while migrating and/or post-arrival. This retrospective cohort study explored vaccination rates among migrant and non-migrant children in New Zealand (NZ). Linked de-identified data from various government sources from 1 January 2006 to 31 December 2015 were analysed using Statistic NZ's Integrated Data Infrastructure. Vaccination rates were compared between three cohorts of children aged up to 5 years: foreign-born children who migrated to NZ; children born in NZ of migrant mothers; and a comparator group of children born in NZ to non-migrant mothers. Less than half of foreign-born children (46%) had a record in the NZ National Immunisation Register compared with 95% and 96% among migrant and non-migrant NZ-born children, respectively. Foreign-born migrant children had lower age-appropriate reported vaccination rates by vaccine of interest, ethnicity and visa category compared with NZ-born children. Migrant children from Pacific ethnicities had lower reported coverage than other ethnicities. High rates of not age-appropriately vaccinated were noted among foreign-born children on refugee, Pacific and humanitarian visa schemes. This study highlights possible shortfalls around immunisation data, particularly about recording vaccinations given overseas for foreign-born children, and potential challenges around engagement with immunisation services for migrant children. However, results highlight the successful engagement of quota refugee children as part of NZ's refugee orientation programme. It is important to monitor vaccination coverage by migrant and refugee background to inform improvements to policy and practice for wider population health benefits.